Going Digital A Strategic Guide for Small Businesses to Scale Through E-Commerce - Zulfikar; Azka Friday (Journal Bisnis Digital dan Inovasi Manajemen, 2026)
The rapid expansion of the digital economy has transformed e-commerce from an optional sales channel into a critical survival and scaling mechanism for Small and Medium Enterprises (SMEs). Despite its immense potential, many traditional small businesses struggle to transition online due to technical, financial, and strategic hurdles. This article provides a comprehensive, actionable framework designed to guide SMEs through a successful digital migration. Utilizing a mixed-methods approach, the study analyzes the primary barriers to digital adoption and identifies key success factors, including platform selection, supply chain digitization, and data-driven digital marketing. The findings reveal that structured digital onboarding significantly lowers operational risks and enhances revenue diversity for small businesses. Ultimately, this paper serves as a strategic roadmap for entrepreneurs to effectively leverage e-commerce ecosystems, transition from local operations to broader markets, and achieve sustainable long-term growth in an increasingly digitalized economy.